The detecting of damage conductor with guided image filter - Ismail, .; Kamarul Hawari, Ghazali; Surfa, Yondri; Firdaus, .; Yefriadi, .; Nasrul, Harun (IOP Publishing, 2020)
The Damage of electrical conductor of high voltage transmission system is very common. This problem effected the distribution of electrical power from the sources into the costumer place. The main cause of this problem if come from the damage of electrical conductor. There were many ways to detect damage conductor so far. The most common is through compute the impedance of transmission line. This method is accurate, but it needs to switch of the line for a while. This disruption contribute losses for the costumers and energy provider. In order to handle this problem, our proposed method is to detect the damage conductor with Guided Image Filter. The input image is a visible image and the reference image is invisible image. The processing is very simple. The result obtained has high accuracy. The accuracy is shown on the detecting map.